Pengaruh Shopee Paylater, Endorsment, Dan Sikap Tabzir Terhadap Impulse Buying Pada Produk Kosmetik - Khoiriah Amalia Siregar; Tuti Anggraini; Atika Atika (Universitas Labuhanbatu, 2023)
Nowadays, it is not uncommon for students to collect various beauty products so that from day to day the existing cosmetic products are also more varied and increasingly in demand. In determining a suitable product, of course, students tend to choose randomly without first finding out which product they need. So the student will buy the same type of product more than one to try it first and then will determine which product is more suitable for him. In this case, the characteristics of unplanned purchases (impulse buying) are caused by the stimulation of the shopping environment, such as the ease of online shopping payment methods with one of the shopee paylater applications, and also due to the superiority of the products delivered in cosmetic product endorsement ads, consumers will be willing to sacrifice something to get the cosmetic products they want instead of the cosmetic products they need. This study used a survey method by distributing questionnaires to 107 respondents. Sampling technique in this study is probability sampling. The analysis used in this study is a multiple linear regression analysis. The results showed that partially variable shopee paylater (X1), endorsement (X2), and attitude tabzir (X3), significant effect on impulse buying on cosmetic products among students of the Faculty of Economics and Islamic Business UINSU because significant value < 0.05. This obtained a significant value of shopee paylater 0.042, endorsement 0.004, and tabzir attitude 0.017. The effect of shopee paylater variables partially on student buying interest is 31.0%, endorsement variables are 28.2%, and tabzir attitude variables are 23.8%. Simultaneously variable shopee paylater (X1), endorsement (X2), and attitude tabzir (X3). Significant effect on the buying interest of students of the Faculty of Islamic Economics and business with a significant value of 0.000 < 0.05 and the effect of 41.9%.